Activation and allosteric regulation of the orphan GPR88-Gi1 signaling complex - Chen, Geng; Xu, Jun; Inoue, Asuka; Schmidt, Maximilian; Bai, Chen; Lu, Qiuyuan; Gmeiner, Peter; Liu, Zheng; Du, Yang (Nature Communications, 2022)
GPR88 is an orphan class A G-protein-coupled receptor that is highly expressed in the striatum and regulates diverse brain and behavioral functions. Here we present cryo-EM structures of the human GPR88-Gi1 signaling complex with or without a synthetic agonist (1R, 2R)-2-PCCA. We show that (1R, 2R)-2-PCCA is an allosteric modulator binding to a herein identified pocket formed by the cytoplasmic ends of transmembrane segments 5, 6, and the extreme C terminus of the α5 helix of Gi1. We also identify an electron density in the extracellular orthosteric site that may represent a putative endogenous ligand of GPR88. These structures, together with mutagenesis studies and an inactive state model obtained from metadynamics simulations, reveal a unique activation mechanism for GPR88 with a set of distinctive structure features and a water-mediated polar network. Overall, our results provide a structural framework for understanding the ligand binding, activation and signaling mechanism of GPR88, and will facilitate the innovative drug discovery for neuropsychiatric disorders and for deorphanization of this receptor.
CRIS-Team Scopus Importer:2022-05-20